Experimental data for the slug two-phase flow characteristics in horizontal pipeline - Mohmmed, A.O. (Elsevier Inc., 2018)
The data presented in this article were the basis for the study reported in the research articles entitled âStatistical assessment of experimental observation on the slug body length and slug translational velocity in a horizontal pipeâ (Al-Kayiem et al., 2017) 1 which presents an experimental investigation of the slug velocity and slug body length for air-water tow phase flow in horizontal pipe. Here, in this article, the experimental set-up and the major instruments used for obtaining the computed data were explained in details. This data will be presented in the form of tables and videos. Â© 2017 The Authors